INVESTIGASI TERHADAP LAMANYA PENYELESAIAN AUDIT: BUKTI EMPIRIS DARI PERUSAHAAN-PERUSAHAAN PUBLIK DI BEI - Rifki Dahlan; Dyah N A Janie (Solusi, 2020)
This research investigates on audit delay factors. Audit delay is important issue for its ability to affect the timeliness of accounting information release. There are eight factors used in this research: company size (using market value I market capitalization as its proxy}, level of company profitability, auditor's opinion, industry classification, company that announced loss, accountant firm size, multinational company, number ofyears company has been a client of public accountant firm. There are 288 manufacturing and banking/financial public companies listed in Indonesia Stock Exchange (IDX)selected using (purposive) judgment sampling method for period 2007-2009, using multiple regression analysis in this study. The result shows that audit delay is irfluenced by company size and industry classification. This evidence suggest that only two of eight factors wich are significantly influencing audit delay. Further analysis also reveals that several studies using larger sample result in more significant variables, while others using smaller sample result in less significant variables.Keywords: audit delay, company size, market value (market capitalization}, level of company profitability, auditor's opinion, industry classification, company that announced loss, accountant firm size, multinational company, number of years company has been a client of public accountant firm.